Identity and intercultural competence: probing student experiences in Malaysian campuses - Syarizan Dalib,; Minah Harun,; Norhafezah Yusof, (Penerbit Universiti Kebangsaan Malaysia, 2017)
This study offers a Malaysian perspective on identity and intercultural competence. We examine how ethnically diverse students in Malaysian campuses make sense of their identities and intercultural competence. Using communication theory of identity as the underlying theoretical framework, we explore their discourse on identity and intercultural competence based on their experiences with cultural others. We collect data from in-depth interviews with selected participants. The study reveals two themes: the affiliation nature of identity and the dynamic nature of identity. The analysis contributes to enriching current understanding of intercultural competence that takes into account identity and intercultural experiences in Malaysia.